Improving Student Learning Outcomes Using Images in SKI Learning at MTs 12 Indramayu - Kharis Musya’fa (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research was motivated by low scores in the History of Islamic Culture subject, with learning outcomes still lacking and low. This study aimed to improve student learning outcomes through classroom activities, teacher activities, and student activities. To achieve this, images were chosen as a learning medium, believed to improve student learning outcomes. This study was a classroom action research using observational methods and data collection techniques to assess learning outcomes. This study identified 32 students with low integrity in the History of Islamic Culture subject, with 22 students (69%) achieving or above the Minimum Completion Criteria (KKM), while 10 students (31%) were still below the Minimum Completion Criteria (KKM). This was due to many students being lazy, not paying attention or not understanding when the teacher explained the material, some appeared unenthusiastic, and others were very busy in class. Although the material presented by the teacher seemed less engaging due to the lack of media, the material presented by the teacher appeared less engaging.